Navigating artificial intelligence in education : first- and second-order barriers to the implementation of AI in Finnish classrooms - Le Bihan, Eeva (2024)
This qualitative study explores the barriers that Finnish primary and secondary school teachers’ perceived while implementing AI education in their classrooms. The data used for the study was generated using semi-structured interviews with nine teachers. The participants were all part of the Innokas-network project “Tekoäly nyt!” The analysis mostly focused on explicit mentions of barriers, but some second-order barriers were found within more implicit contexts. The analysis method was an abductive form of thematic analysis. In the interviews teachers described the barriers they had faced while imple- menting AI education. The teachers expressed that they had encountered barriers during the project, especially relating to the limited amount of software they could use without issues with information security policies. Lack of time was also perceived as a barrier to the implemention of AI education in the classroom. First- order, or external, barriers were in general more explored in this study, perhaps due to the approach taken. Second-order, or internal, barriers were, however, also somewhat explored in this study, and many teachers did not only have trouble with their work hours and workload, but also with having time to implement everything in the classroom while often prioritizing other content such as mathematics and even referring to AI education in ways that could be interpreted as less important than other content. The results shed light on the areas in which AI education implementation needs improvement, which is especially important in a time where AI proficiency is becoming more important in people’s everyday lives.